Landscape Features Affecting Northern Bobwhite Predator-Specific Nest Failures in Southeastern USA - Susan N. Ellis-Felege; Shannon E. Albeke; Nathan P. Nibbelink; Michael J Conroy; D. Clay Sisson; William E. Palmer; John P. Carroll (National Quail Symposium Proceedings, 2017)
Nest predation is a critical component in avian productivity and typically is the leading cause of nest failure for most birds. Several landscape features are thought to drive the behavioral interaction between northern bobwhite (Colinus virginianus; e.g., nest placement) and their predators (e.g., search methods for food acquisition). In order to understand habitat characteristics influencing predation, we studied bobwhite nests using 24-hour near-infrared video cameras. We monitored 675 bobwhite nests with cameras on 3 properties in northern Florida and southern Georgia, USA, during 2000–2006. To test the association between nest failures and specific failure causes with landscape structure, we calculated a suite of landscape metrics and examined these at 3 spatial scales (3.1 ha, 19.6 ha, and 50.3 ha). We found increased probability of nest success with greater proportions of, and proximity to, fallow and annually disked fields at larger scales (50.3 ha), but we found no landscape metrics to be important predictors of bobwhite nest failures at small scales (<20 >ha). Fallow and disked fields may provide alternative prey items (e.g., rodents) important in buffering nest predation. Relative to meso-mammal predation, we observed increases in proportion of the landscape in field to be related to lower incidental nest failures at the smallest scale (3.1 ha). Nests closer to feed lines were more likely depredated by meso-mammals than ants at the 2 larger spatial scales. Interestingly, the fate of a nest was independent of the fate of neighboring nests, suggesting bobwhite nest predation may be primarily incidental.
Keywords: colinus virginianus; northern bobwhite; Florida; Georgia; landscape metrics; nest camera; nest predation